Black Boarding Academies as a Prudential Reparation - Roy Brooks (Columbia Journal of Race and Law)
With billions of dollars pledged and trillions of dollars demanded to redress slavery and Jim Crow (“Black Reparations”) the question of how best to use these funds has moved into the forefront of the ongoing campaign for racial justice in our post-civil rights society.  Reparatory strategies typically target the norms and structures that sustain racial disadvantage wrought by slavery and Jim Crow. The goal of such transitional reparations is to extinguish the menace of white supremacy and systemic racism across the board.  Restructuring in housing, education, employment, voting, law enforcement, health care, and the environment—social transformation—is absolutely needed in the United States if the race problem is ever to be resolved. That much is clear beyond peradventure.  The hard question, however, is whether Black Reparations can take us there. Are Black Reparations (or reparations in general) powerful enough to engineer social transformation, or what in this case would be “transitional racial justice”? Unfortunately, I do not believe they can. The American race problem is simply too big for reparations to fix. It would take decades of massive amounts of government spending and the sustained moral commitment of the American people to achieve transitional racial justice in this country. The inflationary impact of the requisite spending (estimated at $6.4 trillion to $59.2 trillion) would give opponents of reparations an easy target. Moreover, transitional reparations have rarely been attempted in other countries and when tried it has never succeeded to my knowledge. South Africa attempted to use reparations for social transformation. While there has been a transformation of political power, giving Black South Africans a strong voice in the government, economic power remains in the hands of White South Africans and racial discrimination in housing and education continues. Although at one time I was among scholars who had hoped Black Reparations could deliver a much-needed Third Reconstruction, I would be remiss as a passionate supporter of Black Reparations for many decades to ignore the cold facts—reparations have never successfully reconstructed a society.